Pengaruh Likuiditas, Ukuran Perusahaan, Kinerja Perusahaan Terhadap Harga Saham Dimoderasi Oleh Opini Audit Pada Perusahaan Makanan Dan Minuman - Rifa Nadira Fulliani; Yusuf Faisal; Siti Rahma Hanifah Royani (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2022)
The purpose of this study was to analyze the effect of liquidity, company size, company performance on stock prices moderated by audit opinion on food and beverage companies listed on the Indonesia Stock Exchange 2013-2018. The time period of this research is 2013-2018, with the sampling technique using purposive sampling. The number of samples that meet the criteria is 13 companies from 32 food and beverage companies listed on the Indonesia Stock Exchange during this research period. This research uses quantitative methods with data analysis methods using multiple linear regression analysis with the classical assumption test first. By testing the hypothesis using partial significance test (t test) and simultaneous significance test (F test) and the coefficient of determination (Adjusterd R2) processed with the output eviews. The results of this research title explain that liquidity, company size, company performance. Simultaneously liquidity has a significant effect on stock prices with a significance level, firm size has no effect on stock prices, Company performance has a positive and significant effect on stock prices, Audit opinion moderates liquidity affects stock prices, Audit opinion moderates the size of the company and affects stock prices, Audit opinion moderates the company's performance. stock price.